2007
DOI: 10.1128/aac.00209-07
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the GraRS Two-Component System with the VraFG ABC Transporter To Support Vancomycin-Intermediate Resistance in Staphylococcus aureus

Abstract: Current treatment for serious infections caused by methicillin-resistant Staphylococcus aureus relies heavily upon the glycopeptide antibiotic vancomycin. Unfortunately, this practice has led to an intermediate resistance phenotype that is particularly difficult to treat in invasive staphylococcal diseases, such as septicemia and its metastatic complications, including endocarditis. Although the vancomycin-intermediate resistance phenotype has been linked to abnormal cell wall structures and autolytic rates, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
239
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(253 citation statements)
references
References 56 publications
10
239
1
3
Order By: Relevance
“…The locus has also been called aps because of its more general antimicrobial-peptide-sensing capacity (180). The overexpression of GraR or GraS results in a slight increase in the MIC of vancomycin (57), and a knockout mutation results in hypersensitivity (122,204). However, in two different instances, point mutations have resulted in increased resistance to vancomycin, presumably by modifying the activity of the proteins (60,123).…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The locus has also been called aps because of its more general antimicrobial-peptide-sensing capacity (180). The overexpression of GraR or GraS results in a slight increase in the MIC of vancomycin (57), and a knockout mutation results in hypersensitivity (122,204). However, in two different instances, point mutations have resulted in increased resistance to vancomycin, presumably by modifying the activity of the proteins (60,123).…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%
“…Mutations, inactivation, and altered expression of graRS have been linked to changes in vancomycin susceptibility in S. aureus (57,60,111,123,204,225). GraRS (Aps) is known to control the dltABCD operon, which controls the alanylation of wall teichoic acids in response to antimicrobial challenge, indicating that the structure of teichoic acids can change in response to challenges (111,180,181).…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%
“…Although our screen and follow up validation used tunicamycin concentrations that are two orders of magnitude below those that inhibit MraY, we wanted to confirm key results using a fully genetic approach that did not rely on a small molecule (10). This step seemed necessary because some of the knockouts, including ΔdltA, ΔgraR, and ΔvraFG, are known to have increased susceptibility to cationic antimicrobial peptides (CAMPs) and certain other antibiotics with cell envelope targets (7,8,25). Increased susceptibility is proposed to occur because the cell surface lacks the D-alanine modifications that normally repel positively charged toxins at the envelope interface (26).…”
Section: Linkage Analysis Provided Gene-gene Validation Of Compound-genementioning
confidence: 99%
“…cytochrome c (Cyt c), calculated pI 10.0 Meehl et al, 2007;Matsuo et al, 2011)). Subsequently the bacteria are removed by centrifugation and the amount of these substances remaining in the supernatants is determined fluorometrically (GFP) or photometrically (Cyt c), for example.…”
Section: Methods For Assessing Bacterial Cell Surface Charge Propertiesmentioning
confidence: 99%
“…However, in the Bce-like systems it has been shown that the BceS-like HKs are not the sensors of the stimulus by itself, but instead depend on the ATP driven transport of the substrate by the cognate ABC transporter for signal transduction (Bernard et al, 2007;Meehl et al, 2007;.…”
Section: How Is the Stimuli Sensed By Bce-like Systems?mentioning
confidence: 99%